Earliest observation of the tetracycline destructase tet(X3) - Frédéric Grenier; Simon Lévesque; Sébastien Rodrigue; Louis-Patrick Haraoui (Microbiology Spectrum, 2024)
ABSTRACTTigecycline is an antibiotic of last resort for infections with carbapenem-resistant Acinetobacter baumannii. Plasmids harboring variants of the tetracycline destructase gene tetX promote rising tigecycline resistance rates. We report the earliest observation of tet(X3) in a clinical strain predating tigecycline’s commercialization, suggesting selective pressures other than tigecycline contributed to its emergence.IMPORTANCEWe present the earliest observation of a tet(X3)-positive bacterial strain, predating by many years the earliest reports of this gene so far. This finding is significant as tigecycline is an antibiotic of last resort for carbapenem-resistant Acinetobacter baumannii (CRAB), which the World Health Organization ranks as one of its top three critical priority pathogens, and tet(X3) variants have become the most prevalent genes responsible for enabling CRAB to become tigecycline resistant. Moreover, the tet(X3)-positive strain we report is the first and only to be found that predates the commercialization of tigecycline, an antibiotic that was thought to have contributed to the emergence of this resistance gene. Understanding the factors contributing to the origin and spread of novel antibiotic resistance genes is crucial to addressing the major global public health issue, which is antimicrobial resistance.